Analysis of Fish Consumption Pattern of People in Jombang District, East Java, during Pandemic and Endemic Covid-19 - Rahmawati, Rahmawati; Sanjaya, Yushinta Aristina; Asih, Sri Alam Syah Lihan Candra; Putri, Ardita; Putri, Rinjani Eko; Ayuningtyas, Diella Trisna; Mulyani, Dwi (Journal of Marine and Coastal Science, 2023)
Fishery resources are a good source of food for human health. The fisheries sector plays a role in food security, not only as a complement but also plays a role in fulfilling food, nutrition, and protein sources, as well as people's income. Food security is closely related to the continuity of fish supply to meet people's needs. In this study the method used was survey method with the type of research used was descriptive research with a quantitative approach and data collection techniques in this study by conducting a survey using a questionnaire. The low consumption of fish in the community is caused by a lack of public knowledge about information on the nutritional content and benefits of consuming fish. The survey results stated that 89.3% of the respondents already knew the benefits of fish and the remaining 10.7% did not know the benefits of fish. As much as 85.4% of the people of Jombang District, East Java, get fish by buying it themselves at traditional markets with 80.6% liking fresh fish products and 19.4% liking processed fish products. As many as 79.6% of the people of Jombang District, East Java consider the quality of fish before buying fish; 45.6% stated that the ease of obtaining fish was their consideration in buying fish; and 50.5% stated price as their consideration in buying fish. As many as 83.5% of respondents stated that there was no difference in fish consumption patterns before and after the pandemic era. After the pandemic, people's frquency in consuming fish has increased, although not significantly. This is possibly due to the start of a sense of public awareness of the body's nutritional needs after the pandemic era.